Evaluating the Factors Affecting the Adoption of Management Information Systems from Users’ Perspective: An Empirical Study - Altuhaifi, Mohammed Saleh; CHOUK, Souad Kamoun (The Arab Journal of Administration, 2025)
The study aims to identify the factors that affect the adoption of management information systems in Yemeni telecom enterprises. To achieve the objectives of the study, the descriptive analytical approach was used, and the questionnaire was adopted as a basic tool for collecting data from respondents. The study sample was selected using the simple random sampling method, and the size of the research sample was 369 employees. The data were analyzed using statistical methods based on SPSS and AMOS structural equation modeling software. The study reached a number of results, the most important of which are: There is no statistically significant relationship between information quality and the dependent variable: adoption of management information systems, while there is a statistically significant positive relationship between the rest of the variables of the proposed study (attitude toward using the system, user training, system quality) and adopting management information systems. It also concluded that the factors influencing the successful adoption of management information systems may be organizational, individual, or technological factors. The study also reached a set of conclusions and recommendations, the most prominent of which are: the importance of providing a comprehensive and clearer vision of the importance of the role of systems in institutions to enable users to realize the benefits resulting from this to enhance their positive attitudes towards accepting the use of the system, the need to pay attention to improving the quality of the system to ensure user satisfaction and enhance his confidence in relying on it. The need to conduct more studies for a broader understanding of the process of adopting management information systems, and to identify other.